Modeliranje razslojene atmosfere v eksperimentalni napravi jedrske elektrarne s popisom z zgoščenimi parametri - Kljenak, Ivo (Strojniški vestnik, 2006)
In this paper we describe the modelling of a non-homogeneous multi-component atmosphere in a multi-compartment nuclear power plant containment using a lumped-parameter approach. The modelling is applied to the topic of hydrogen behaviour in the containment at accident conditions. The main benefit of the proposed approach is the possibility of modelling the phenomena in complex, multi-compartment containments. As an illustration, the experiment E11.2 "Hydrogen distribution in loop flow geometry", which was performed in the integral experimental facility "Heissdampf Reaktor" (HDR) in Germany, was simulated. A lumped-parameter input model of the HDR facility was developed for the computer code CONTAIN. The calculated pressure, temperature and hydrogen concentrations are compared to experimental values. A good qualitative prediction of the atmosphere stratification was achieved, which supports the adequacy of the lumped-parameter approach.
Keywords: jedrska tehnika; modeli zgoščenih parametrov; mešanje; razslojevanje; CONTAIN